Students’ Perception Towards Flashcards as Media to Assist Their Vocabulary Mastery in Junior School - Yohana Nurmala; Maman Suryaman (Peneliti.net, 2022)
The ability to speak English is important because this ability has an impact academically. English ability can be seen from the vocabulary that a person has. One of the creative efforts in making learning interesting is using flash card media. This study aims to examine the student's perspective on flashcards as a medium to help their vocabulary mastery in junior high school. This research method is descriptive qualitative using a narrative inquiry approach. The research subjects were 3 students from one of the schools in East Jakarta in grade 9 junior high school. The results of this study are Students have expressed positive perceptions about using flashcards as media used in learning, including reasons, methods, and advantages and disadvantages. In addition, that most students gave positive responses to the use of flashcards as a media to help them in mastering vocabulary, students felt happy, useful by using flashcards as a learning companion, effective in using them, and supporting students' metacognitive development.